Miracles: Their Concept and Identification - Schulz, Heiko (Toronto journal of theology, 2017)
The first two parts of this article are an attempt to conceptually clarify what we mean by saying that something is a miracle. I will argue that perceiving or experiencing an event as a divine act is not only necessary, but also sufficient for considering it a miracle. In the final paragraph I will try to show that, as a subclass of events, miracles share with the former what I call their self-authenticating character—a character whose uniqueness explains and accounts for their privileged accessibility and identification from a first-person perspective.